An ‘Open’ Method for 3D Modelling and Mapping in Underwater Archaeological Sites - Skarlatos, Dimitrios; Demestiha, Stella; Kiparissi, Stavroula (My University, 2012)
Underwater photogrammetry is a difficult task by definition. When time limits are imposed on both acquisition and processing time, it becomes even more complicated. In addition when resources are limited and the main deliverable should be a complete 3D model, only a novel method may match the requirements. Under the aforementioned conditions, a new method using a combination of photogrammetry and computer vision techniques was utilised using open source software to face demands
Keywords: Underwater; Archaeology; Computer vision; Photogrammetry; 3D reconstruction; Open software